Penerapan Prinsip Good Corporate Governance Terhadap Budaya Indonesia Menurut Prespektif Islam - Ridaniar Kharisma; Qurrota A’yunina; Mohamad Djasuli (CV. ITTC INDONESIA, 2022)
In this 21st century era of change, implementing good corporate governance (GCG) has become an urgent task for all large and medium-sized organizations. In this case, it is impossible to distinguish between large and medium enterprises. The GCG philosophy exists, but the implementation is different. The implementation of GCG itself refers to the allocation or distribution of strengths and responsibilities as well as results and accountability for the performance or success of the organization. Qualitative methods are used in this study and GCG principles are used in this study to analyze Indonesian culture according to Islamic law. Good corporate governance can be interpreted as good management practices. The application of the concept of good governance in Indonesia cannot be separated from the organizational culture itself. According to the Islamic concept, business management takes over the value system contained in the Qur'an. Al-Baqarah verses 282-283 of the Qur'an explains the importance of accounting so that no party is treated unfairly. We apply 5 principles that are in line with Indonesian culture and Islamic law, namely: Transparency, Accountability, Accountability, Independence, Honesty. Which is carried out continuously and continuously and is evaluated periodically by the GCG implementers themselves. Islam is implemented in GCG principles. Good corporate governance can be interpreted as good management practices. The application of the concept of good governance in Indonesia cannot be separated from the organizational culture itself. According to the Islamic concept, business management takes over the value system contained in the Qur'an. Al-Baqarah verses 282-283 of the Qur'an explains the importance of accounting so that no party is treated unfairly.